Devolution and Party Organisation in the UK: Statewide parties and statewide-regional branch relations over candidate selection in Scotland and Wales - Jonathan Bradbury (Territorial Party Politics in Western Europe, 2009)
The chapter forms part of a research collection designed to pioneer the study of political decentralisation and political parties. This particular chapter focuses on clarifying the theoretical literature that should drive research of political decentralisation and party decentralisation in party organisation and tests hypotheses in the literature against the case of devolution and party organisation in the UK related to power over candidate selection. It compares across elections and across the three major British-wide parties. It provides conclusions on the UK case which revise earlier literature on central and local power in parties over candidate selection in the Uk as well as its implications for studing political decentralisation and party organisation comparatively.